The impact of servicescape on customer satisfaction and customer loyalty of Hotel Puri Melaka / Tun Frisha Fazara Zulkarnain - Zulkarnain, Tun Frisha Fazara (2009)
This research study has been conducted at Hotel Puri Melaka. This research is a study on “the impact of Servicescape on customer satisfaction and customer loyalty”. The main objective of this study is to examine the impact of physical facilities, ambient condition, interpersonal condition and location of Hotel Puri towards customer satisfaction and customer loyalty. There are four servicecape’s variables (Physical Facility, Ambient Condition, Location and Interpersonal Condition) under the servicescape components that measures visitors’ satisfaction. Moreover, positive word of mouth, repurchasing intention, and recommending to others are the three attributes that measure visitors’ level of loyalty. The researcher has adopted the descriptive research in order to conduct the research on the issue. The researcher’s sampling design is the Nonprobability sampling which is the Convenience Sampling Technique and 100 questionnaires were distributed to the visitors of Hotel Puri which refers to the local and international target population of the research. The questionnaires were distributed at the entrance, registration counter and the lobby of Hotel Puri Melaka by the researcher. The researcher adopts Scientific Program of Social Science (SPSS) application to analyze the data that is gathered throughout the research process in order to obtain accurate answer for the questions. From the findings, it can be concluded that most of the visitors are satisfied and loyal towards servicescape of Hotel Puri Melaka.